INVESTIGATION PROCESS OF PERPETRATORS OF MOBILE PHONE THEFT BASED ON RESTORATIVE JUSTICE (CASE STUDY AT BATU POLICE) - Ilham Fauzi Prakoso; Budi Parmono; Moh. Muhibbin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Indonesian legal system recognizes the term criminal justice system as a system of law enforcement aimed at resolving and overcoming criminal cases that occur in society. The purpose of the criminal justice system is not only to process the settlement of criminal cases that are fast, inexpensive, and short but also to provide human rights protection, respect the principle of presumption of innocence and the process of punishment that provides a balance of law, defendants and victims. In dealing with these conditions, it takes the rules that underlie the settlement of criminal cases by promoting the principles of justice, expediency, and legal certainty. The Republic of Indonesia Police Agency is the main key in determining whether or not a criminal case can proceed into a criminal justice process, in this case issuing the Republic of Indonesia State Police Regulation Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice. The author conducted research on the case resolution process carried out by the Batu Police in handling theft cases and whether the settlement process has realized restorative justice. The rule can be used as a reference by investigators in conducting mediation outside the court by using the development of the principle of restorative justice, which means returning to normal before the crime took place.